The beginning and project process of the original source of the Fisheries Ministery. Permanence and trascendence as a public building - Vargas Quispe, César A. (2023)
This article is both a testimony and an analysis of the project routes used to design the original headquarters of the Ministry of Fisheries in Lima (1970-1976). The understanding of the iconic and multifunctional building begins by knowing what attributes have made its permanence and transcendence possible. The article addresses, on the one hand, the design concerns that gave rise, in the sixties of the last century, to a hot scene, where modern architecture in Peru was in search of new forms of expression. This was associated with the seismic phenomenon that occurred in Lima in that decade. On the other hand, it evidences the conjunctural determinations of a structural order (political agents, social customs, among others) and contingents (conformation of the Rodrigo, Cruchaga & Soyer company and the 1966 earthquake) that are interrelated with the origin and process of the architectonic project of this building.